ナンキョク ショウワキチ ダイ10 キョジュウトウ モクシツ パネル ノ マゲ キョウド シケン - 半貫, 敏夫; ハンヌキ, トシオ; 高橋, 弘樹; タカハシ, ヒロキ; 石鍋, 雄一郎; イシナベ, ユウイチロウ; 佐野, 雅史; サノ, マサシ; 平山, 善吉; ヒラヤマ, ゼンキチ; Hannuki, Toshio; Takahashi, Hiroki; et al. (2002)
P(論文) 南極昭和基地で約29年間使われてきた居住棟の主要構造部品、屋根、壁、床の各木質パネルの耐久性を評価するための曲げ強度試験を行った。その結果外気に接するパネルの構成材に部分的劣化が認められ、それが構造強度に影響していることが確かめられた。パネルの強度は総体的に落ちているとはいえ、設計強度はまだ十分に維持しており、南極で安全に使用できる構造性能を保っていることが確かめられた。 実験結果を整理すると、南極のような極限環境にある木質サンドイッチパネルの耐久性設計では、表面合板の保全が構造上最も重要な課題であることが分かった。 The old living hut was built by the 10th Japanese Antarctic Research Expedition (JARE-10) in 1969. Since then, it had been used continuously at Syowa Station in Antarctica. In 1998, the living hut was taken apart, which were taken back to Japan. To estimate the durability of the prefabricated wooden structural elements, namely, roof panels, wall panels and floor panels, the bending strength of the elements was tested. Structural performances of these elements were decreased little by little. Deterioration of the surface of the panels was marked on the outside part of the elements. The required strength of the elements for the structural design was adequate, although the strength was decreased as a whole. It was found that surface protection of the structural wooden panel from erosion is most important to preserve the structural performance. departmental bulletin paper